CMOS : circuit design, layout, and simulation - Baker, R. Jacob, 1964- (Hoboken, N.J. : Wiley-IEEE Press, 2010)
'The third edition of CMOS: Circuit Design, Layout, and Simulation continues to cover the practical design of both analog and digital integrated circuits, offering a vital, contemporary view of a wide range of analog/digital circuit blocks, the BSIM model, data converter architectures, and much more. The 3rd edition completes the revised 2nd edition by adding one more chapter (chapter 30) at the end, which describes on implementing the data converter topologies discussed in Chapter 29. This additional, practical information should make the book even more useful as an academic text and companion for the working design engineer. Images, data presented throughout the book were updated, and more practical examples, problems are presented in this new eition to enhance the practicality of the book'--
'The third edition of CMOS: Circuit Design, Layout, and Simulation continues to cover the practical design of both analog and digital integrated circuits, offering a vital, contemporary view of a wide range of analog/digital circuit blocks, the BSIM model, data converter architectures, and much more'--
Includes bibliographical refrences and index
Keywords: Metal oxide semiconductors, complementary -- Design and construction; Integrated circuits -- Design and construction; Metal oxide semiconductor field-effect transistors